New Strategy for Uhamka Sustainability Post COVID-19 Pandemic - Sutarman, Asep; Rahayu, Dewi Pudji; Setiawan, Edi; Marlena, Leni; Ul Albab, Farah Nisa (International Journal of Indonesian Business Review, 2023)
This study aims to analyze how conditions during the Covid pandemic and new strategic steps affect sustainability. We use the inferential verification technique, which is a strategy used by researchers to assess the validity of the presented hypothesis by collecting actual data from alumni, lecturers, students, partners, parents, leaders and education staff of Universitas Muhammadiyah Prof. DR. HAMKA Jakarta. A total of 222 research samples were deliberately selected as respondents. We used Structural Equation Modeling (SEM) analysis, assisted by Smart PLS software version 3.2. for quantitative analysis to test the hypothesis and for qualitative analysis obtained based on the results of interviews with several parties related to the UHAMKA Jakarta as a material for discussion in the research. Several findings were found: (1) the Covid pandemic condition had a significant positive effect on the new strategy; (2) the new strategy has a significant positive effect on sustainability; and (4) the new strategy has a mediating function in the influence of the Covid-19 pandemic condition on the sustainability of the University of Muhammadiyah Prof. DR. HAMKA Jakarta. The limitation of this research is that the survey only focuses on the University of Muhammadiyah Prof. DR. HAMKA Jakarta only. Practical implications: According to research findings, new strategies are needed to increase sustainability in urgent situations, for example during the Covid-19 pandemic. By implementing and implementing the new strategy, the sustainability of the university as an educational institution will be better maintained. The new strategy variable proved to be a mediating or intervening variable for the Covid-19 pandemic condition in influencing the sustainability of the University of Muhammadiyah Prof. DR. HAMKA Jakarta. University of Muhammadiyah Prof. DR. HAMKA Jakarta must be able to adapt to a new life after a pandemic through a crisis period so that it can maintain its sustainability in the future.